Epidemiological, clinical, therapeutic and evolutive aspects of bacterial meningoencephalitis - Carlos Olivers Cobian Caballero; Lázaro Ibrahim Romero García; Mirtha Laguna Delisle; Justo Luis Filiú Ferrera (Centro Provincial de Información de Ciencias Médicas, 2016)
A descriptive and observational serial cases study, was carried out in 45 patients with bacterial meningoencephalitis, discharged from "Saturnino  Lora Torres" Teaching Clinical Surgical Provincial Hospital, from 2008  to 2013, in order to characterize them according to epidemiological, clinical, microbiological and evolutive variables. In the series the female sex prevailed (54.5%). Among the cardinal symptoms of the disease there were: fever (81.8%), migraine (77.3%) and meningeal signs (75.0%). It was not possible to obtain isolation in 52.3% of the affected patients, what was achieved in those with Streptococcus pneumoniae(38.7%).  A mortality of 18.2% was estimated, associated directly to the presence of systemic sepsis.